STUDY OF ELECTRICAL INSTALLATION PLANNING AT PRATAMA JAGOI BABANG HOSPITAL - Dian, Mardiana; Pontia W, F. Trias; Arsyad, M. Iqbal (Faculty of Engineering, Universitas Tanjungpura, 2023)
Planning for Jagoi Babang Pratama Hospital is a Regional General Hospital owned by the Government which is located in Jagoi Babang District, Bengkayang Regency, West Kalimantan Province. Jagoi Babang Primary Hospital has a total land area of 10,275 m2. The Study of Electrical Installation Planning at Pratama Jagoi Babang Hospital will be carried out in Building C, which at the time this research was appointed, development planning was being carried out and the location of Building C was on the 1st floor. The construction of this hospital is very dependent on electrical installations, especially lighting and air conditioning installations to support the needs of hospital staff and patients. For the smooth running of hospital activities, calculations are needed to design correct and proper electrical installations, according to the Indonesian National Standard based on General Electrical Installation Requirements (PUIL) of 2011 and Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2016 concerning technical requirements for hospital buildings and infrastructure which is stated in article 23. In planning the electrical installation of Pratama Jagoi Babang Hospital, researchers made several calculations, namely lighting illumination, air conditioning capacity, safety size, cross-sectional area, total load, and voltage drop. Based on the results of calculations and analysis of the number of lamps counted, 470 lamps were obtained with the type of DL LED 14 Watt, DL LED 18 Watt, TL LED 18 Watt. Then the total load required is 8168 Watt = 8.168 kW while for planning Air Conditioners with a total load required is 140.633 kW with a total of 35 Air Conditioners.